2011
DOI: 10.1093/ndt/gfr359
|View full text |Cite
|
Sign up to set email alerts
|

Early nephrology consultation can have an impact on outcome of acute kidney injury patients

Abstract: In AKI, patients evaluated by nephrologists seem to be more seriously ill than those not evaluated and present similar mortality rate. The delayed nephrology consultation can be associated with increased ICU mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
85
2
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(93 citation statements)
references
References 17 publications
4
85
2
2
Order By: Relevance
“…Our study promotes a culture of recording and reporting changes in hourly urine output for critically ill patients. If hourly urine output is documented, electronic alert mechanisms could be developed to actively survey for oliguria and facilitate patient assessment, fluid or vasopressor administration, nephrology specialist consultation, or early RRT before additional biochemical evidence of AKI is observed (32,33). Evaluating pretest probability using a 3-hour oliguria cutoff may aid in the decision to deploy other diagnostic tests (e.g., AKI biomarkers), potentially increasing their accuracy and cost-effectiveness (34).…”
Section: Discussionmentioning
confidence: 99%
“…Our study promotes a culture of recording and reporting changes in hourly urine output for critically ill patients. If hourly urine output is documented, electronic alert mechanisms could be developed to actively survey for oliguria and facilitate patient assessment, fluid or vasopressor administration, nephrology specialist consultation, or early RRT before additional biochemical evidence of AKI is observed (32,33). Evaluating pretest probability using a 3-hour oliguria cutoff may aid in the decision to deploy other diagnostic tests (e.g., AKI biomarkers), potentially increasing their accuracy and cost-effectiveness (34).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the development of effective therapeutic maneuvers for the prevention or early treatment of AKI have been impeded by late diagnosis of this disorder. 5 We undertook a multicentre cohort study to characterize the incidence and outcomes of AKI in an unselected cohort of patients admitted to Canadian intensive care units (ICUs). Among the patients with AKI, we sought to identify clinical predictors of mortality at the time of AKI diagnosis.…”
Section: Résumémentioning
confidence: 99%
“…Similarly, Perez-Valdivieso et al (4) reported that an increase of Ͼ100% in serum creatinine level at the time of nephrology consultation was associated with higher mortality and impaired renal recovery on discharge. Most recently, Ponce et al (5) have confirmed these findings in 148 ICU patients with AKI at a Brazilian teaching hospital. Nephrology consultation was delayed (Ն48 hours) in 62.3%, which was associated with increased ICU mortality (65.4% versus 88.2%, P Ͻ 0.001).…”
mentioning
confidence: 73%